Calcitonin gene-related peptide: a potential protective agent in cerebral ischemia–reperfusion injury - Xiong, Jie; Wang, Zhiyong; Bai, Junhui; Cheng, Keling; Liu, Qicai; Ni, Jun (Frontiers in Neuroscience, 2023)
Ischemic stroke is the most common type of cerebrovascular disease with high disability and mortality rates, which severely burdens patients, their families, and society. At present, thrombolytic therapy is mainly used for the treatment of ischemic strokes. Even though it can achieve a good effect, thrombolytic recanalization can cause reperfusion injury. Calcitonin gene-related peptide (CGRP) is a neuropeptide that plays a neuroprotective role in the process of ischemia-reperfusion injury. By combining with its specific receptors, CGRP can induce vasodilation of local cerebral ischemia by directly activating the cAMP–PKA pathway in vascular smooth muscle cells and by indirectly activating the NO–cGMP pathway in an endothelial cell-dependent manner,thus rapidly increasing ischemic local blood flow together with reperfusion. CGRP, as a key effector molecule of neurogenic inflammation, can reduce the activation of microglia, downregulates Th1 classical inflammation, and reduce the production of TNF-α, IL-2, and IFN-γ and the innate immune response of macrophages, leading to the reduction of inflammatory factors. CGRP can reduce the overexpression of the aquaporin-4 (AQP-4) protein and its mRNA in the cerebral ischemic junction, and play a role in reducing cerebral edema. CGRP can protect endothelial cells from angiotensin II by reducing the production of oxidants and protecting antioxidant defense. Furthermore, CGRP-upregulated eNOS can further induce VEGF expression, which then promotes the survival and angiogenesis of vascular endothelial cells. CGRP can also reduce apoptosis by promoting the expression of Bcl-2 and inhibiting the expression of caspase-3. These effects suggest that CGRP can reduce brain injury and repair damaged nerve function. In this review, we focused on the role of CGRP in cerebral ischemia-reperfusion injury.